2007
DOI: 10.1002/per.613
|View full text |Cite
|
Sign up to set email alerts
|

Well‐being and the accessibility of pleasant and unpleasant concepts

Abstract: The trait–congruency hypothesis predicts that persons high in positive or negative trait affect more readily process pleasant or unpleasant stimuli, respectively. In two studies, participants were administered measures of personality and affect. Moreover, a yes/no lexical decision task with pleasant, unpleasant and neutral words was administered in Study 1, whereas a go/no‐go task was used in Study 2. Several methods to increase reliabilities of differences in reaction times are explored. Correlations of measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 49 publications
4
33
1
Order By: Relevance
“…The average percentage of error trials among the remaining participants ( N = 46) was low ( M = 3.06, SD = 2.62). Following recommendations by Borkenau and Mauer (2007), attention indices were calculated with individually trimmed mean latencies: Each participant's 10% slowest responses were considered outliers. The internal consistency of the injustice‐related attention index, determined by difference scores for the two test blocks, was low (α = .34) but considerably higher than those usually reported for the visual probe task or reaction time measures in general (cf.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The average percentage of error trials among the remaining participants ( N = 46) was low ( M = 3.06, SD = 2.62). Following recommendations by Borkenau and Mauer (2007), attention indices were calculated with individually trimmed mean latencies: Each participant's 10% slowest responses were considered outliers. The internal consistency of the injustice‐related attention index, determined by difference scores for the two test blocks, was low (α = .34) but considerably higher than those usually reported for the visual probe task or reaction time measures in general (cf.…”
Section: Resultsmentioning
confidence: 99%
“…The internal consistency of the injustice‐related attention index, determined by difference scores for the two test blocks, was low (α = .34) but considerably higher than those usually reported for the visual probe task or reaction time measures in general (cf. Borkenau & Mauer, 2007; Schmukle, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14] see also [6]). For example, it has been shown that typical happy people perceive, categorize, and retrieve pleasant information more readily, more easily than typical unhappy people, and may even interpret ambiguous stimuli more favorably [15,16]. In the same manner, an anxiety-related responses bias [17] and also an attention bias resulting in interpretation of ambiguous stimuli as threatening ones have been noticed in typical anxious individuals [18].…”
Section: Emotional Categorization: Individual Differences and Lateralmentioning
confidence: 72%